Beyond the Sum of Its Parts : Combining Financial Instruments to Support Low-Carbon Development - World Bank (Washington, DC, 2017)
The world development report 2010 estimates that an additional $200 billion per year of climate-related financing is needed in developing countries between now and 2030 to keep global average temperature rise within 2 degrees Celsius. Developing countries face increased financing challenges over coming decades as they seek to pursue economic development along a lower emission trajectory. The goal of this paper is twofold: i) to provide greater information and clarity on these three mitigation-related climate financing instruments available for the World Bank Group (WBG) and their application in the context of specific projects and national policy frameworks; and ii) to draw lessons for the broader development community on how resources from different climate financing instruments can be combined for expanded impact, increased leverage, and enhanced efficiency. This paper represents an initial contribution to this field and will be followed by papers focusing on guarantees for low-carbon growth support for the private sector and the challenges of financing climate resilience and adaptation.